Experimental and Theoretical Study of a New Technique for Mixing Self-Compacting Concrete with Marble Sludge Grout - Rayed Alyousef; Mohamed Amine Khadimallah; Chokri Soussi; Omrane Benjeddou; Malek Jedidi (Advances in Civil Engineering, 2018)
Currently, marble waste is valued by incorporating powders, obtained by drying and grinding sludge resulting from marble blocks cutting operation, or the aggregates, obtained by crushing the solid waste, on self-compacting concrete. These two procedures require a lot of energy. This experimental and theoretical work focuses on the direct incorporation of marble sludge in self-compacting concrete. The first part needs the study of the rheological behavior of the marble sludge grout (MSG) as a function of the added water amount. For this, different grouts were prepared and tested by varying the water/sludge ratio. In the second part, four self-compacting concretes (SCCs) were mixed with MSG having different water/sludge ratios in order to validate a new technique of gassing self-compacting concrete with MSG. The test results show that the marble grains of grout is totally dispersed when the water/sludge ratio was equal to 1.2. The results also show that the gassing with MSG allows us to obtain SCC having both self-compacting property and self-leveling property compared to SCC made by adding marble filler to the cementitious matrix.